Faktor Penyebab Banyaknya siswa/i Yang Kurang Lancar Membaca Al Qur'an Dan Kurangya Semangat Dalam Mempelajari Ilmu Agama Di SMP Swasta Al-Ikhlas - Munawir Pasaribu; Kasbiadi kasbiadi (Cattleya Darmaya Fortuna, 2022)
The purpose of this writing is to give us knowledge, what causes children to not be able to read the Qur'an and iqro' in this day and age, and any factors that influence the lack of children to learn religion in particular. And how or how to deal with it.